ANALISIS KEBIJAKAN KIP-K DAN PROBLEMATIKNYA - Muhamad Iqbal Deswara; Dena irawan; Salma Dwiyanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The KIP Kuliah policy program plays an important role in improving the quality of education in Indonesia. The research method used is qualitative with data collection techniques in the form of interviews. The aim of this research is to ensure that students who experience problems in the registration process for the KIP K program receive a solution. This research shows that there are still many students who experience problems in the KIP Kuliah registration process. The research concluded that there were several inputs that could be a solution to overcome this problem, such as improving the greeting website to improving the quality of service in each village for making SKTM